Production performance of indigenous chicken of northeastern region and improvedvarieties developed for backyard farming - HAUNSHI, SANTOSH; DOLEY, SUNIL; SHAKUNTALA, I (The Indian Journal of Animal Sciences, 2011)
The present study was conducted to evaluate the production performance of indigenous Miri type and improved varieties like Gramapriya and Vanaraja maintained at the Institute farm. All three genetic groups were evaluated for weekly body weight from 0 day to 8 weeks of age, biweekly body weight from 8 to 14 weeks of age and at 20 and 40 weeks of age; feed intake and feed conversion ratio (FCR.) up to 8 weeks of age; age at sexual maturity; egg production rate, shank and keel length and egg quality traits at 40 weeks of age. There were significant differences among all 3 genetic groups for body weights, keel and shank length, sexual maturity, egg production rate, egg weight, egg quality traits such as shell thickness, specific gravity and albumen index. Miri type had significantly early sexual maturity, better shell thickness, higher specific gravity and egg production rate (40 weeks), lesser feed intake and better FCR than the improved varieties. On the other hand improved varieties had significantly higher body weight at different ages, shank and keel length, egg weight (at sexual maturity and 40 weeks of age), and better egg production rate during 40 to 52 weeks of age. Among improved varieties, Vanaraja had significantly higher body weight, shank and keel length, higher feed intake and better FCR than the Gramapriya variety while Gramapriya had better egg production rate, early sexual maturity and higher egg mass. There were no significant differences between Vanaraja and Gramapriya for body weight at day-old and egg weight (at sexual maturity and 40 weeks of age). The study concluded that indigenous chicken could perform better than improved varieties for certain economic traits under same management and rearing conditions.